Determinants of Neonatal and Post-neonatal Mortality in Pakistan (The Pakistan Development Review, 2002)
Ensuring the survival and well being of children is a concern of families, communities and nations throughout the world. Since the turn of the 20th century infant and child mortality in more developed countries has steadily declined and, currently, has been reduced to almost minimal levels. In contrast, although infant and child mortality has declined in the past three decades in most less developed countries, the pace of change and the magnitude of improvement vary considerably from one country to another. The inverse relationship between socio-economic variables of the parents and infant and child mortality is well established by several studies [Muhuri (1995); Forste (1994); Hobcraft, et al. (1984); Caldwell (1979); Sathar (1985, 1987)] and it holds true irrespective of the overall level of mortality in the national populations [Ruzicka (1989)]. The influence of parental education on infant and child health and mortality has proved to be universally significant [Bicego and Boerma (1993); Caldwell, et al. (1990)]. The father’s education, mother’s education and their work status each have independent effects upon child survival in developing countries [Sandiford, et al. (1995); Forste (1994); Caldwell, et al. (1983)]. Economic conditions of the household also help in explaining the variation in infant and child mortality. The nature of housing, diet, access to and availability of water and sanitary conditions as well as medical attention all depend on the economic conditions of the household. For example, poor families may reside in crowded, unhygienic housing and, thus, suffer from infectious disease associated with inadequate and contaminated water supplies and with poor sanitation [Esrey and Habicht (1986)].